Rise and Evolution of Design Thinking Research for Business Innovation (2024)
As organizations are increasingly demanding faster and more successful innovations in the markets, design thinking (DT) has established itself as a generative approach or methodology for solving complex problems and as a driver for the development of products and services that offer superior value to users. To understand this phenomenon, this exhaustive review has been carried out through a scientometric analysis of DT for innovation, examining annual scientific production, country-specific contributions, journal publications, and collaboration networks between authors. The results allow us to identify a growing interdisciplinary interest in the applicability of DT for business innovation. The United States is the country that stands out in academic production, while Germany and Italy concentrate the most important academic networks. Using the Tree of Science (ToS) metaphor, three subtopics were identified as current trends in the field: DT for innovation activities within the business sector, applicability and contributions of DT in other sectors, and DT as a learning and innovation methodology. This study provides a framework for understanding the evolution and current state of design thinking and thus for projecting future research and new applications of design thinking as an approach to innovation in increasingly diverse fields.